2015
DOI: 10.1113/jp271219
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin does not prevent increases in myofibrillar or mitochondrial protein synthesis following endurance exercise

Abstract: Key pointsr Previous studies have shown that endurance exercise increases myofibrillar (MyoPS) and mitochondrial (MitoPS) protein synthesis in skeletal muscle.r The mechanistic target of rapamycin (mTOR) is considered to be a key intracellular nutrient-sensing protein complex, which activates MyoPS in response to anabolic stimuli.r Little is known regarding the regulation of MyoPS and MitoPS in response to endurance exercise.r In the present study, we show that MyoPS and MitoPS increase in skeletal muscle foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 45 publications
7
58
3
Order By: Relevance
“…Together, the data show that both HFD and VWR have distinct effects on phosphorylation of these downstream mTORC1 substrates. Furthermore, the findings support the notion that S6K and 4E-BP1 phosphorylation states undergo differential regulation depending on environmental and physiological conditions, including response to HFD and VWR exercise (4346). …”
Section: Discussionsupporting
confidence: 79%
“…Together, the data show that both HFD and VWR have distinct effects on phosphorylation of these downstream mTORC1 substrates. Furthermore, the findings support the notion that S6K and 4E-BP1 phosphorylation states undergo differential regulation depending on environmental and physiological conditions, including response to HFD and VWR exercise (4346). …”
Section: Discussionsupporting
confidence: 79%
“…However, in a recent study, administration of rapamycin to mice was found to amplify the increase in PGC-1␣ mRNA caused by 1 h of running, suggesting an inverse relationship between mTORC1 activity and PGC-1␣ (23). Nonetheless, the lack of any effect of leucine alone on the PGC-1␣4 response, despite its stimulatory effect on mTORC1 signaling ( Fig.…”
Section: Effects Of Exercise and Intake Of Amino Acids On The Levels mentioning
confidence: 81%
“…The role of REDD1 in regulating the nutrient-and contraction-induced stimulation of mTORC1 and protein synthesis is relatively well explored, whereas there is a paucity of consistent data pertaining to its role during aerobic exercise. A single bout of treadmill aerobic exercise increases REDD1 mRNA and protein in the gastrocnemius of male rats as well as male and female mice (51,89,99). In mice, the increase in REDD1 protein appeared to coincide with repressed mTORC1 signaling, whereas in rats, mTORC1 signaling was increased in parallel with elevated REDD1 protein (51,99).…”
Section: Role Of Redd1 During Physiological Conditionsmentioning
confidence: 98%
“…A single bout of treadmill aerobic exercise increases REDD1 mRNA and protein in the gastrocnemius of male rats as well as male and female mice (51,89,99). In mice, the increase in REDD1 protein appeared to coincide with repressed mTORC1 signaling, whereas in rats, mTORC1 signaling was increased in parallel with elevated REDD1 protein (51,99). In humans, a single 20-min bout of submaximal aerobic exercise on a cycle ergometer at an intensity of 1.2 W/kg (ϳ50% of the subjects' V O 2 max ) failed to change REDD1 protein in the vastus lateralis, wheereas mTORC1 signaling was blunted (81).…”
Section: Role Of Redd1 During Physiological Conditionsmentioning
confidence: 99%